Developmental social pragmatic interventions for preschoolers with autism spectrum disorder: A systematic review. (January 2019) - Binns, Amanda V; Oram Cardy, Janis
Background and aims: Developmental social pragmatic interventions are one treatment option for supporting the social communication and language skills of preschool children with autism spectrum disorder. Our first aim was to differentiate interventions using a developmental social pragmatic model from other developmental or naturalistic behavioral approaches. We applied explicit criteria outlining core features of developmental social pragmatic interventions to identify programs that use these core features. We then systematically reviewed studies examining the impact of developmental social pragmatic interventions in supporting (a) foundational social communication and language skills of preschool children with autism spectrum disorder and (b) caregiver interaction style. Additionally, we reviewed results exploring mediators and potential factors influencing children's response to developmental social pragmatic interventions. Methods: A multistep comprehensive search strategy was used to identify developmental social pragmatic treatments and studies examining their effectiveness for preschool children with autism spectrum disorder. The characteristics of each study and their outcomes were then reviewed, and a modified Critical Appraisal Skills Programme tool was used to evaluate rigor. Main contribution/Results: Six interventions that met criteria to be classified as developmental social pragmatic are examined within this review. Ten studies of varying methodological rigor met criteria for inclusion and collectively reported on the outcomes of 716 preschool-aged children with autism spectrum disorder. All of the studies examined foundational communication outcomes and all but one reported positive outcomes for at least one of the measures. Seven studies examined language outcomes. While results were positive for language use within natural contexts, they were mixed for overall, receptive, and expressive language. Parents' interaction styles significantly changed postintervention, namely in terms of increased responsiveness, synchronous behavior, use of affect, and decreased directiveness. Only two studies conducted formal mediation analysis and found that parent responsiveness and synchronous behavior were related to children's positive response to treatment. Conclusions: This review suggests that developmental social pragmatic treatments positively impact children's foundational communication capacities (i.e. attention, social referencing, joint attention, initiation, reciprocity). Positive findings were not consistently found for supporting children's language. Further, methodologically rigorous studies are needed to draw definitive conclusions. Additional research exploring components of developmental social pragmatic treatments that might mediate response to treatment is needed. Implications: This review provides synthesized information for clinicians, families, and researchers on the effectiveness of developmental social pragmatic interventions for improving children's foundational communication. It also suggests directions for future research and provides ideas for enhancing methodological rigor and promoting more homogeneity among treatment implementation and outcome assessments.